Machine Learning Algorithms in Predicting College Students’ Grades: A Review - Brzozka, Bartlomiej (Journal of Applied Automation Technologies, 2025)
With the advancement of education informatization, colleges and universities have accumulated a huge amount of student learning data. The application of machine learning algorithms in the prediction of student performance in colleges and universities has become a research hotspot in the field of education, which is capable of mining the potential laws in the data and providing support for educational decision-making. In this paper, we review relevant studies at home and abroad, analyze the current status of the application of machine learning algorithms in student performance prediction, focus on the principles, applications, advantages and disadvantages of commonly used machine learning algorithms, and discuss the advantages and limitations of the study, and finally look forward to the future direction of development, with a view to providing reference for educators and researchers, and helping to improve the quality of education.